The derivative of ${{\sec }^{-1}}\left( \dfrac{1}{2{{x}^{2}}-1} \right)$ with respect to $\sqrt{1-{{x}^{2}}}$ at $x=\dfrac{1}{2}$ is
A. $-4$
B. 4
C. 2
D. $-2$
Answer
Verified
381.9k+ views
Hint: We first define the chain rule and how the differentiation of composite function works. We differentiate the main function with respect to the intermediate function and then differentiation of the intermediate function with respect to $x$. We take multiplication of these two different differentiated values.
Complete step-by-step solution:
We need to find the derivative of ${{\sec }^{-1}}\left( \dfrac{1}{2{{x}^{2}}-1} \right)$ with respect to $\sqrt{1-{{x}^{2}}}$ at $x=\dfrac{1}{2}$ using chain rule.
We assume $x=\cos \alpha $ and by putting the value we get $2{{x}^{2}}-1=2{{\cos }^{2}}\alpha -1=\cos 2\alpha $.
So, ${{\sec }^{-1}}\left( \dfrac{1}{\cos 2\alpha } \right)={{\sec }^{-1}}\left( \sec 2\alpha \right)=2\alpha $.
From inverse law we get $\alpha ={{\cos }^{-1}}x$. So, $2\alpha =2{{\cos }^{-1}}x$.
Here we assume the function is $m\left( x \right)=2{{\cos }^{-1}}x$ and the other function is $n\left( x \right)=\sqrt{1-{{x}^{2}}}$.
We need to find ${{\left[ \dfrac{dm}{dn} \right]}_{x=\dfrac{1}{2}}}$. We express it as $\dfrac{dm}{dn}=\dfrac{dm}{dx}\times \dfrac{1}{\dfrac{dn}{dx}}$.
\[\dfrac{dm}{dx}=\dfrac{d}{dx}\left[ 2{{\cos }^{-1}}x \right]=-\dfrac{2}{\sqrt{1-{{x}^{2}}}}\]
\[\dfrac{dn}{dx}=\dfrac{d}{dx}\left[ \sqrt{1-{{x}^{2}}} \right]=\dfrac{-2x}{2\sqrt{1-{{x}^{2}}}}=-\dfrac{x}{\sqrt{1-{{x}^{2}}}}\]
We place the values of the differentiations and get
\[\begin{align}
& \dfrac{dm}{dn} \\
& =\dfrac{dm}{dx}\times \dfrac{1}{\dfrac{dn}{dx}} \\
& =\left( -\dfrac{2}{\sqrt{1-{{x}^{2}}}} \right)\times \left( \dfrac{1}{-\dfrac{x}{\sqrt{1-{{x}^{2}}}}} \right) \\
& =\dfrac{2\sqrt{1-{{x}^{2}}}}{x\sqrt{1-{{x}^{2}}}} \\
& =\dfrac{2}{x} \\
\end{align}\]
Now the value of ${{\left[ \dfrac{dm}{dn} \right]}_{x=\dfrac{1}{2}}}$ will be \[{{\left[ \dfrac{2}{x} \right]}_{x=\dfrac{1}{2}}}=\dfrac{2}{\dfrac{1}{2}}=4\]. The correct option is B.
Note: We need remember that in the chain rule \[\dfrac{d}{d\left[ h\left( x \right) \right]}\left[ goh\left( x \right) \right]\times \dfrac{d\left[ h\left( x \right) \right]}{dx}\], we aren’t cancelling out the part \[d\left[ h\left( x \right) \right]\]. Canceling the base differentiation is never possible. It’s just a notation to understand the function which is used as a base to differentiate.
Complete step-by-step solution:
We need to find the derivative of ${{\sec }^{-1}}\left( \dfrac{1}{2{{x}^{2}}-1} \right)$ with respect to $\sqrt{1-{{x}^{2}}}$ at $x=\dfrac{1}{2}$ using chain rule.
We assume $x=\cos \alpha $ and by putting the value we get $2{{x}^{2}}-1=2{{\cos }^{2}}\alpha -1=\cos 2\alpha $.
So, ${{\sec }^{-1}}\left( \dfrac{1}{\cos 2\alpha } \right)={{\sec }^{-1}}\left( \sec 2\alpha \right)=2\alpha $.
From inverse law we get $\alpha ={{\cos }^{-1}}x$. So, $2\alpha =2{{\cos }^{-1}}x$.
Here we assume the function is $m\left( x \right)=2{{\cos }^{-1}}x$ and the other function is $n\left( x \right)=\sqrt{1-{{x}^{2}}}$.
We need to find ${{\left[ \dfrac{dm}{dn} \right]}_{x=\dfrac{1}{2}}}$. We express it as $\dfrac{dm}{dn}=\dfrac{dm}{dx}\times \dfrac{1}{\dfrac{dn}{dx}}$.
\[\dfrac{dm}{dx}=\dfrac{d}{dx}\left[ 2{{\cos }^{-1}}x \right]=-\dfrac{2}{\sqrt{1-{{x}^{2}}}}\]
\[\dfrac{dn}{dx}=\dfrac{d}{dx}\left[ \sqrt{1-{{x}^{2}}} \right]=\dfrac{-2x}{2\sqrt{1-{{x}^{2}}}}=-\dfrac{x}{\sqrt{1-{{x}^{2}}}}\]
We place the values of the differentiations and get
\[\begin{align}
& \dfrac{dm}{dn} \\
& =\dfrac{dm}{dx}\times \dfrac{1}{\dfrac{dn}{dx}} \\
& =\left( -\dfrac{2}{\sqrt{1-{{x}^{2}}}} \right)\times \left( \dfrac{1}{-\dfrac{x}{\sqrt{1-{{x}^{2}}}}} \right) \\
& =\dfrac{2\sqrt{1-{{x}^{2}}}}{x\sqrt{1-{{x}^{2}}}} \\
& =\dfrac{2}{x} \\
\end{align}\]
Now the value of ${{\left[ \dfrac{dm}{dn} \right]}_{x=\dfrac{1}{2}}}$ will be \[{{\left[ \dfrac{2}{x} \right]}_{x=\dfrac{1}{2}}}=\dfrac{2}{\dfrac{1}{2}}=4\]. The correct option is B.
Note: We need remember that in the chain rule \[\dfrac{d}{d\left[ h\left( x \right) \right]}\left[ goh\left( x \right) \right]\times \dfrac{d\left[ h\left( x \right) \right]}{dx}\], we aren’t cancelling out the part \[d\left[ h\left( x \right) \right]\]. Canceling the base differentiation is never possible. It’s just a notation to understand the function which is used as a base to differentiate.
Recently Updated Pages
Master Class 12 English: Engaging Questions & Answers for Success
Master Class 12 Chemistry: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Class 12 Question and Answer - Your Ultimate Solutions Guide
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Trending doubts
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
Explain sex determination in humans with the help of class 12 biology CBSE
Give 10 examples of unisexual and bisexual flowers
Distinguish between asexual and sexual reproduction class 12 biology CBSE
Explain Mendels Monohybrid Cross Give an example class 12 biology CBSE
What is the mechanism of halogenations of alkanes class 12 chemistry CBSE